2010
DOI: 10.1016/j.wem.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Status in Rats After Intermittent Exposure to Hypobaric Hypoxia

Abstract: The absence of significant differences between groups indicates that our IHH program has little impact on the general redox status, even in the laboratory rat, which is more sensitive to hypoxia than humans. We conclude that IHH does not increase oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
(69 reference statements)
2
10
1
Order By: Relevance
“…On the contrary, Esteva et al (2010) did not find significant differences in the oxidative stress parameters in animals submitted to intermittent hypobaric hypoxia (5000 m). Although we found a significant increment in plasma protein oxidation after 21 days of hypoxic exposure, administration of vitamin C did not prevent it.…”
contrasting
confidence: 61%
“…On the contrary, Esteva et al (2010) did not find significant differences in the oxidative stress parameters in animals submitted to intermittent hypobaric hypoxia (5000 m). Although we found a significant increment in plasma protein oxidation after 21 days of hypoxic exposure, administration of vitamin C did not prevent it.…”
contrasting
confidence: 61%
“…Under hypoxia and during exercise, the increased level of ROS induces an increase of erythrocyte mass, contributing to the organism's adaptation to such conditions. However, excessive amounts of ROS as a result of an imbalance in the pro-and antioxidant systems induce oxidative damage in cells and tissues, which is termed oxidative stress [2]. Erythrocytes, the unique carriers of oxygen, are constantly exposed to ROS due to their function in the organism.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia exposure has also been combined with normal athletic training in a variety of ways [48]. More specifically, IHH exposure has been shown to be an efficient stimulus for eliciting different adaptive responses so as to improve peripheral oxygen supply [49,50]. Serebrovskaya et al reported similar results with a normobaric hypoxia exposure programme that was able to enhance innate immunity by mobilizing progenitor cells, activating neutrophils and by increasing circulating complement and immunoglobulins [33].…”
Section: Discussionmentioning
confidence: 99%